PU.1 and IRF8 Modulate Activation of NLRP3 Inflammasome via Regulating Its Expression in Human Macrophages - Yashiro, Takuya; Yamamoto, Machiko; Araumi, Sanae; Hara, Mutsuko; Yogo, Kyoko; Uchida, Koichiro; Kasakura, Kazumi; Nishiyama, Chiharu (Frontiers in Immunology, 2021)
NLRP3 inflammasomes play crucial roles in the initiation of host defense by converting pro-Caspase-1 to mature Caspase-1, which in turn processes immature IL-1 and IL-18 into their biologically active forms. Although NLRP3 expression is restricted to monocytic lineages such as monocytes, macrophages, and dendritic cells, the mechanisms determining the lineage-specific expression of NLRP3 remain largely unknown. In this study, we investigated the transcription factors involved in cell-type-specific transcription of NLRP3. We found that a distal, rather than a proximal, promoter of human NLRP3 was predominantly used in the human monocytic cell lines and macrophages. Reporter analysis showed that an Ets/IRF composite element (EICE) at -309/-299 and an Ets motif at +5/+8 were critical for transcriptional activity of the distal promoter. Electrophoretic mobility shift assays and chromatin immunoprecipitation assays demonstrated that two transcription factors, PU.1 and IRF8, both of which play essential roles in development and gene expression of the monocytic lineage, were bound to the EICE site, whereas PU.1 alone was bound to the Ets site. Knockdown of PU.1 and/or IRF8 mediated by small interfering RNA downregulated expression of NLRP3 and related molecules and markedly diminished the LPS-induced release of IL-1 in THP-1, suggesting that activity of the NLRP3 inflammasome was suppressed by knockdown of PU.1 and IRF8. Taken together, these results indicate that PU.1 and IRF8 are involved in the monocytic lineage-specific expression of NLRP3 by binding to regulatory elements within its promoter and that PU.1 and IRF8 are potential targets for regulating the activity of the NLRP3 inflammasome.